SCHOOL PRINCIPALS’ LEADERSHIP IN THE DEVELOPMENT OF TEACHER RESOURCES QUALITY - ningsih, rita (Universitas Pendidikan Indonesia, 2020)
The existence of school principals both as learning leaders and as leaders of educational institutions is very important and strategic, because the principal is the top leader as well as the top manager in an education unit that will give color and determine the direction of achieving educational and learning goals at school. This study aims to describe the Principal's leadership in developing the quality of teacher resources in Ar Raihan Middle School and Darul Fattah Middle School in Bandar Lampung. The results showed that teacher personality development is carried out by empathizing and establishing; Developing teacher knowledge enhancement is done through several activities such as educative socialization and implement open management; Teacher guidance in an effort to understand and implement the vision and mission of the school is done through the socialization of the School Work Plan; The development of the teacher's ability to make decisions is done by empowering the work mechanism through the School Management Team for Ar Raihan Middle School, while the Darul Fattah Middle School through the founders of the school and the School Internal Quality Development Team; Fostering the ability of teachers to communicate both verbally and in writing in the school environment.